Alteration in gut microbiota is associated with immune imbalance in Graves’ disease - Liu, Yalei; Tang, Shasha; Feng, Yu; Xue, Binghua; Cheng, Chaofei; Su, Yong; Wei, Wei; Zhang, Lijun; Huang, Zhoufeng; Shi, Xiaoyang; Fang, Yuanyuan; Yang, Junpeng; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Background Graves’ disease (GD), characterized by immune aberration, is associated with gut dysbiosis. Despite the growing interest, substantial evidence detailing the precise impact of gut microbiota on GD’s autoimmune processes remains exceedingly rare. Objective This study was designed to investigate the influence of gut microbiota on immune dysregulation in GD. Methods It encompassed 52 GD patients and 45 healthy controls (HCs), employing flow cytometry and enzyme-linked immunosorbent assay to examine lymphocyte and cytokine profiles, alongside lipopolysaccharide (LPS) levels. Gut microbiota profiles and metabolic features were assessed using 16S rRNA gene sequencing and targeted metabolomics. Results Our observations revealed a disturbed B-cell distribution and elevated LPS and pro-inflammatory cytokines in GD patients compared to HCs. Significant differences in gut microbiota composition and a marked deficit in short-chain fatty acid (SCFA)-producing bacteria, including ASV263(Bacteroides), ASV1451(Dialister), and ASV503(Coprococcus), were observed in GD patients. These specific bacteria and SCFAs showed correlations with thyroid autoantibodies, B-cell subsets, and cytokine levels. In vitro studies further showed that LPS notably caused B-cell subsets imbalance, reducing conventional memory B cells while increasing naïve B cells. Additionally, acetate combined with propionate and butyrate showcased immunoregulatory functions, diminishing cytokine production in LPS-stimulated cells. Conclusion Overall, our results highlight the role of gut dysbiosis in contributing to immune dysregulation in GD by affecting lymphocyte status and cytokine production.